EFFECTIVE STRATEGIES FOR TEACHING ENGLISH IN A MULTILINGUAL CLASSROOM - Dosmambetova, M.A.; Narshabaeva, A.Yu. (SCIENCE and SOCIETY, 2025)
This article explores the challenges and strategies involved in teaching English to multilingual students, emphasizing cognitive, social, and cultural factors that influence language acquisition. It aims to provide educators with effective approaches to create inclusive learning environments that cater to the unique needs of these learners. By recognizing the diverse linguistic backgrounds of multilingual students, teachers can better support their language development and academic success.